Creative Steps for Learning Islamic Religion (Classroom Management Study at Smk Muhammadiyah 2 Wates) - Muhammad Rizky Nur Risam; Arif Agus Mujahidin; Nanik Rahmanti; Fifin Al-Fionita; Sri Roviana (Universitas Muhammadiyah Yogyakarta, 2023)
This research aims to learn and understand more deeply related to the creative learning and class management steps carried out by Islamic Religious Education teachers at SMK Muhammadiyah 2 Wates. This scientific study uses a qualitative descriptive method. Data collection techniques used are observation, interviews, and library research. At SMK Muhammadiyah 2 Wates, researchers suggest that educators' roles and functions are vital in carrying out learning steps and classroom management. Based on the research results, every PAI teacher at Muhammadiyah 2 Wates Vocational School must understand, analyze, make decisions, and be competent in achieving changes in class conditions and student enthusiasm, so that learning can be carried out in a conducive and effective manner.